Provable secure identity-based online/offline encryption scheme with continual leakage resilience for wireless sensor network. (June 2020) - Zhang, Xiujie; Fu, Xingbing; Hong, Lu; Liu, Yu; Wang, Liangliang
As a potential technology, the identity-based online/offline encryption scheme is split into two phases (the offline phase and the online phase) which is especially suitable for sensor nodes with limited computation resources in that most of the works can be executed offline. However, a challenging issue is the well-known identity-based online/offline encryption schemes unable to resist continual key leakage attacks of the secret keys. To address the above security challenge, we put forth the first continual leakage-resilient identity-based online/offline encryption scheme which is suitable for ensuring secure communications in wireless sensor networks. More specifically, our formal security proofs analysis indicates that the proposed scheme can guarantee security even if partial information of the secret key is continually leaked due to side-channel attacks or fault injection attacks. Above all, compared to the existing identity-based online/offline encryption schemes, an identity-based online/offline encryption scheme with continual leakage resilient meets wireless sensor networks with strong security.